PARP inhibitors for cancer therapy - Curtin, Nicola J.; Sharma, Ricky A. (Cancer Drug Discovery and Development, 2015)
PARP Inhibitors for Cancer Therapy provides a comprehensive overview of the role of PARP-poly ADP ribose polymerase-in cancer therapy. The volume covers the history of the discovery of PARP and its role in DNA repair. Additionally, it describes the discovery of the PARP family, and includes a discussion of other DNA maintenance-associated PARPs. As well, the volume features a section on the accessible chemistry behind the development of inhibitors. PARP inhibitors-PARPi-are a group of pharmacological inhibitors that are particularly good targets for cancer therapy. PARP plays a pivotal role in DNA repair and may contribute to the therapeutic resistance to DNA-damaging agents used to treat cancer. Researchers have learned a great deal about the biology of PARP and how tumor-specific defects in DNA repair can be exploited by PARPi. The "synthetic lethality" of PARPi is an exciting concept for cancer therapy, and has led to heightened activity in this area.